Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.6 - Factoring Trinomials - Exercise Set: 77

Answer

$2(x+3)(x-2)$

Work Step by Step

Factoring the $GCF=2$, then the given expression, $ 2x^2+2x-12 $, is equivalent to \begin{array}{l} 2(x^2+x-6) .\end{array} The two numbers whose product is $ac= 1(-6)=-6 $ and whose sum is $b= 1 $ are $\{ 3,-2 \}$. Using these two numbers to decompose the middle term, then the factored form of the expression, $ 2(x^2+x-6) $, is \begin{array}{l}\require{cancel} 2(x^2+3x-2x-6) \\\\= 2[(x^2+3x)-(2x+6)] \\\\= 2[x(x+3)-2(x+3)] \\\\= 2[(x+3)(x-2)] \\\\= 2(x+3)(x-2) .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.